Interim Feed the Future Zone of Influence survey in Tajikistan, 2015 - International Food Policy Research Institute (International Food Policy Research Institute, 2024)
This dataset intends to provide population-based survey data from USAID's Zone of Influence (ZOI) in Tajikistan to perform a midline assessment of its ongoing activities. The dataset consists of interviews with 2,000 households from 12 districts in Khatlon Province, conducted in February and March 2015 in collaboration with Zerkalo Analytics. For the 2015 interim assessment, the IFPRI team attempted to reconstruct the sample from the 2012 FtF FEEDBACK baseline survey in order to create panel data. The questionnaire used for the interim assessment has largely been adapted from FtF FEEDBACK’s baseline survey. For 2015, IFPRI added three new modules on participation in aid programs, migration and remittances, and agriculture. These modules drew upon the designs of recent surveys undertaken by international organizations in the country, including the Tajikistan Living Standards Survey and Tajikistan Jobs Skills Migration Consumption Survey by the World Bank.